The Role of Podcasts in Enhancing Language Learning - Syafei, Muh; Rahman, Rashid; Anis, Nina (Journal International of Lingua and Technology, 2024)
In the digital age, podcasts have emerged as a versatile tool for language learning, offering accessible and engaging content for learners. Despite their growing popularity, there is limited empirical research on how podcasts specifically enhance language acquisition, particularly in diverse educational contexts. This study aims to address this gap by exploring the role of podcasts in improving language skills. This research investigates the effectiveness of podcasts in enhancing language learning outcomes, focusing on listening comprehension, vocabulary acquisition, and learner motivation. A mixed-methods approach was employed, combining quantitative pre- and post-tests with qualitative interviews. Participants included 120 intermediate-level language learners divided into experimental and control groups. The experimental group engaged with podcast-based activities over eight weeks, while the control group followed traditional methods. Data were analyzed using statistical software and thematic analysis. The findings revealed significant improvements in listening comprehension and vocabulary retention among the experimental group. Learners reported increased motivation and autonomy, attributing these gains to the flexibility and authenticity of podcast content. Podcasts are a valuable resource for language learning, fostering both linguistic and motivational benefits. Educators are encouraged to integrate podcasts into curricula to support diverse learning needs.